Menanamkan Jiwa Entrepreneurship Sejak Dini kepada Murid Sekolah Dasar Melalui Program Belajar Mengajar Mengenai Jual Beli dan Promosi - Hendra Maulana; Divana Hikmala Salsabila Puteri; J.A. Jelita Srikandi Pertiwi; Muhammad Nur Salim; Shabirina Laila Azka; Alvina Widya Oktaviani (Institut Nalanda, 2023)
Entrepreneurship is something that everyone should encourage in their children from an early age. Entrepreneurship should be encouraged from a young age so that everyone can develop creative and inventive behavior and character. In terms of community service, we incorporate the entrepreneurial spirit into the activities of the entrepreneurship education teaching and learning process. We chose Sekolah Dasar Negeri 1 Rejoso Kabupaten Nganjuk to inculcate actual entrepreneurship values in elementary school pupils from an early age. Through these teaching and learning activities, all students are expected to understand the transaction tools used in entrepreneurship, the purchasing and selling process, and how to advertise their business items.